Pengaruh Kepemimpinan Transformasional dan Budaya Kerja Terhadap Kompetensi Pedagogik Guru Sekolah Dasar - Nuraeni, Devi; Nurkolis, Nurkolis; Wuryandini, Endang (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study is motivated by issues in teachers’ pedagogical competence, which directly affect the quality of learning. Pedagogical competence is a key ability in designing, implementing, and evaluating learning, yet many teachers still face challenges in its application. Two factors presumed to influence pedagogical competence are principals’ transformational leadership and work culture. The objectives of this study are to examine: (1) the effect of principals’ transformational leadership on teachers’ pedagogical competence, (2) the effect of work culture on teachers’ pedagogical competence, and (3) the simultaneous effect of both factors on the pedagogical competence of elementary school teachers in Pabelan District, Semarang Regency. The research employed a quantitative correlational design. The population consisted of 193 elementary school teachers, with a sample of 130 teachers selected using proportional random sampling. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using classical assumption tests, simple linear regression, and multiple regression. The results revealed that (1) transformational leadership has a significant positive effect on pedagogical competence (t = 10.909 > t-table = 1.978) with a contribution of 48.20% (moderate category); (2) work culture also has a significant positive effect (t = 10.181 > t-table = 1.978) with a contribution of 44.70% (moderate category); and (3) multiple regression analysis confirmed that both variables jointly influence pedagogical competence, contributing 60% (strong category). These findings emphasize that optimal transformational leadership and a solid work culture can significantly enhance teachers’ pedagogical competence.